2012
DOI: 10.1039/c2ob25692d
|View full text |Cite
|
Sign up to set email alerts
|

The origin of global and macrocyclic aromaticity in porphyrinoids

Abstract: The global and macrocyclic aromaticity of porphyrinoids was characterized using our graph theory of aromaticity. The sequential line plots of topological resonance energy (TRE) against the number of π-electrons (N(π)) for different porphyrinoids are similar with four major extrema to those for five-membered heterocycles. This supports the view that five-membered rings are the main origin of global aromaticity in porphyrinoids. Macrocyclic circuits contribute significantly to macrocyclic π-circulation but modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…42 Because the intensity of a ring current is proportional to the area of the circuit, a macrocyclic ring current often looks much larger than aromatic sextet ring currents. Therefore, even though a molecule has a strong paramagnetic ring current, it does not mean that it is globally antiaromatic.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…42 Because the intensity of a ring current is proportional to the area of the circuit, a macrocyclic ring current often looks much larger than aromatic sextet ring currents. Therefore, even though a molecule has a strong paramagnetic ring current, it does not mean that it is globally antiaromatic.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…[3][4][5][6][7] In 1972, Baird predicted that the Hü ckel (anti)aromaticity observed for ground-state systems would become reversed in the lowest triplet state, 8 which was very recently supported by further theoretical calculations [9][10][11][12][13][14][15][16] as well as spectroscopic measurements. [17][18][19] Although macrocyclic (anti-)aromaticity has been frequently observed in many porphyrinoids [20][21][22] and even porphyrin-based nanorings, 23 almost no example of global aromaticity has been observed in benzenoid polycyclic aromatic hydrocarbons because the large resonance energy per p-electron for the benzene ring drives the electrons to predominantly localize at certain benzene rings rather than delocalize to the whole framework in accordance with Clar's sextet rule. 24 One even more challenging goal is to find a global (anti-)aromatic polycyclic hydrocarbon with an annulenewithin-an-annulene (AWA) structure in which the inner ring and outer perimeter behave as if they are independent annulenes, i.e., a ''super-ring'' structure.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the aromatic characteristics of porphyrins (1 a) and related systems remains the topic of considerable debate. [1][2][3] Although porphyrins and related macrocycles are often considered to be examples of bridged annulenes, [4][5][6] some theoretical studies have concluded that the aromatic properties of porphyrinoids are primarily due to the individual pyrrolic rings. [3,7] However, the extent to which the pyrrolic nitrogens contribute to the aromatic properties of porphyrins has been brought into question.…”
mentioning
confidence: 99%
“…[1][2][3] Although porphyrins and related macrocycles are often considered to be examples of bridged annulenes, [4][5][6] some theoretical studies have concluded that the aromatic properties of porphyrinoids are primarily due to the individual pyrrolic rings. [3,7] However, the extent to which the pyrrolic nitrogens contribute to the aromatic properties of porphyrins has been brought into question. [1,2] In particular, dideazaporphyrins 2, which lack these pyrrole-type nitrogens, have been shown to be strongly diatropic and to possess porphyrin-like electronic absorption spectra.…”
mentioning
confidence: 99%